Ice breaker game during the first F2F problem-based learning classroom: enhancing student interaction and teamwork / Nasibah Azme - Azme, Nasibah (2023)
Problem-based learning (PBL) is a teaching method that focusses on student-centred learning (Ali, 2019). The educational goal of PBL is to enable students to develop their analytical, reasoning, problem-solving, and self-learning skills. The PBL in the medical faculty has the potential to help structure basic scientific knowledge in a clinical context and promote generic skills. An effective PBL requires student engagement and interest (Song et al., 2022). A crucial element of PBL is teamwork. Students must work in teams and collaborate to solve the problem and apply knowledge (Fontejin & Dolman, 2019). Due to the Covid-19 pandemic, the Faculty of Medicine at UiTM had implemented hybrid learning for all classes, including PBL. Hybrid learning means students need to join their classes virtually from home at the beginning of the semester, and attend these class in person in the mid- semester.